1998
DOI: 10.1074/jbc.273.29.18332
|View full text |Cite
|
Sign up to set email alerts
|

A Human Homologue of the Schizosaccharomyces pombe rad1+ Checkpoint Gene Encodes an Exonuclease

Abstract: In the fission yeast Schizosaccharomyces pombe the rad1 ؉ gene is required for both the DNA damage-dependent and the DNA replication-dependent cell cycle checkpoints. We have identified a human homologue of the S. pombe rad1 ؉ gene, designated Hrad1, as well as a mouse homologue: Mrad1. Two Hrad1 alternative splice variants with different open reading frames have been identified; one codes for a long form, Hrad1A, and the other encodes a short form because of N-terminal truncation, Hrad1B. Hrad1A has 60% ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 45 publications
3
61
0
Order By: Relevance
“…hRad1, hRad9, and hHus1 Associate in a Checkpoint Complex-Comparisons of the predicted human and yeast protein sequences indicate that the human proteins are 25-30% identical and 53-57% similar to their respective homologs, with homologies extending over extensive portions of each protein (12)(13)(14)(15)(16)(17)(18). In S. pombe, spRad1 and spHus1 associate in wildtype, but not rad9, mutant yeast.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…hRad1, hRad9, and hHus1 Associate in a Checkpoint Complex-Comparisons of the predicted human and yeast protein sequences indicate that the human proteins are 25-30% identical and 53-57% similar to their respective homologs, with homologies extending over extensive portions of each protein (12)(13)(14)(15)(16)(17)(18). In S. pombe, spRad1 and spHus1 associate in wildtype, but not rad9, mutant yeast.…”
Section: Resultsmentioning
confidence: 99%
“…The similarities between yeast and humans extend beyond these proteins, as human homologs of sprad1 (12)(13)(14), sprad9 (15), sprad17 (16), spchk1 (17), and sphus1 (18) genes have been identified, fueling speculation that the checkpoint pathways may be conserved. Despite these advances, the physical and functional roles of these proteins are largely unexplored, even in the well studied yeast systems.…”
mentioning
confidence: 99%
“…The 9-1-1 complex is composed of the RAD9, HUS1 and RAD1 subunits that interact to form a PCNA-like structure that loads on the DNA like a sliding clamp similar to PCNA. It has also been speculated that the 9-1-1 complex functions to generate more ssDNA to enhance checkpoint-associated signaling (Lydall and Weinert, 1995;Parker et al, 1998;Volkmer and Karnitz, 1999;Xu et al, 2001). It will be interesting to see whether and how the RAD16-RFC and 9-1-1 complexes are involved in checkpoint signaling originating from sites of DNA DSBs.…”
Section: General Concepts and Key Playersmentioning
confidence: 99%
“…By yeast two hybrid analysis it was shown that hRad17 interacts with hRad1 (Parker et al, 1998). The checkpoint proteins hRad9, hHus1, and hRad1 can be co-immunoprecipitated with hRad17 from human cell extracts (Rauen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The hRad17/ hRF-C complex is thought to load the 9-1-1 complex onto the DNA at the site of a DNA lesion during an early stage of checkpoint activation (Mitchell, 2001). Recombinant hRad1 and hRad9 purified from E. coli exibit 3'-5'exonuclease activity (Parker et al, 1998;Bessho and Sancar, 2000), suggesting that these proteins might play a role in the processing of DNA lesions.…”
Section: Introductionmentioning
confidence: 99%